Maternal Ureaplasma/Mycoplasma colonization during pregnancy and neurodevelopmental outcomes for preterm infants - Gallini, Francesca; De Rose, Domenico Umberto; Coppola, Maria; Pelosi, Maria Sofia; Cota, Francesco; Bottoni, Anthea; Ricci, Daniela; Romeo, Domenico Marco; Spanu, Teresa; Maggio, Luca; Mercuri, Eugenio; Vento, Giovanni (Frontiers in Pediatrics, 2022)
Introduction Ureaplasma (U.) and Mycoplasma (M.) species have been related to pregnancy complications (including preterm birth) and worse neonatal outcomes. The aim of our work is to evaluate neurodevelopmental outcomes in preterm infants born to mothers with Ureaplasma/Mycoplasma colonization during pregnancy. Methods Preterm infants with gestational age (GA) of ≤ 30 weeks were included in a retrospective follow-up study. To evaluate the effects of maternal vaginal colonization, we divided preterm infants into two groups: exposed and unexposed infants. All infants were assessed at 24 ± 3 months of age using Griffith’s Mental Developmental Scales (GMDS). Results Among 254 preterm infants, only 32 infants (12.6%) were exposed to U. /M. colonization during pregnancy. Exposed infants and unexposed ones had a similar Griffith′s Developmental Quotient (106 ± 27.2 vs. 108.9 ± 19.5, respectively), without significant differences (p = 0.46). However, exposed infants had a significantly poorer outcome than their unexposed peers in terms of locomotor abilities (100.7 ± 28.3 exposed vs. 111.5 ± 26.1 unexposed, p = 0.03). Conclusion For visual and hearing impairment, exposed and unexposed infants had similar incidences of cognitive and motor impairment. However, exposed infants had significantly lower locomotor scores than unexposed peers.